Revealing the Effects of Weak Surfactants on the Dynamics of Surface Fluctuations by Surface Light Scattering - Koller, Thomas Manfred; Kerscher, Manuel; Köksal, Anil; Stockerl, Michael; Klein, Tobias; Fröba, Andreas Paul (Journal of Physical Chemistry B, 2023)
Surfactant monolayers at liquid interfaces induce a viscoelastic behavior that influences the dynamics of surface fluctuations probed by surface light scattering (SLS). Recent thermophysical property research on viscosity and interfacial tension of liquid organic hydrogen carrier (LOHC) systems based on diphenylmethane suggested that such viscoelastic effects may also be present here, although not being expected a priori. To prove the hypothesis that the LOHC intermediate cyclohexylphenylmethane (H6-DPM) can induce a surfactant-like behavior, binary mixtures of diphenylmethane (H0-DPM) or dicyclohexylmethane (H12-DPM) with small amounts of H6-DPM were studied by SLS in combination with conventional viscometry and tensiometry and molecular dynamics simulations between (303 and 473) K. Only in mixtures with H0-DPM which has a slightly larger surface tension than H6-DPM, the presence of the latter compound causes a significant effect on the dynamics of surface fluctuations, especially on their damping. In analogy to the concentration-dependent behavior observed for a monolayer of a highly amphiphilic ionic surfactant on the surface of water at ambient temperature, the orientation of H6-DPM molecules with respect to the surface appears to change from a preferentially perpendicular to a parallel alignment with increasing temperature. This demonstrates that viscoelastic effects including accompanied surface orientation effects can be resolved by SLS even for weakly asymmetric surface-active molecules such as H6-DPM in its diluted mixtures with very similar species.
CRIS-Team Scopus Importer:2023-12-22

Thermophysical properties of the liquid organic hydrogen carrier system based on benzyltoluene considering influences of isomerism and dissolved hydrogen - Kerscher, Manuel; Jander, Julius Hans; Cui, Junwei; Maurer, Lukas A.; Wolf, Patrick; Hofmann, Jonas D.; Köksal, Anil; Zachskorn, Hannah; Auer, Franziska; Schulz, Peter; Wasserscheid, Peter; Rausch, Michael Heinrich; et al. (International Journal of Hydrogen Energy, 2024)
The benzyltoluene (BT)-based liquid organic hydrogen carrier (LOHC) system currently considered for large-scale applications represents a mixture of regioisomers. To characterize this complex system, a comprehensive experimental database for various thermophysical properties of synthesized BT isomers and their mixtures without and with the presence of hydrogen (H2) close to vapor-liquid equilibrium is established using optical and conventional techniques at process-relevant temperatures and pressures up to 573 K and 6 MPa. The surface tension varies by less than 4% among the dehydrogenated (H0-BT) or hydrogenated (H12-BT) isomers. The density and viscosity of mixtures of H0-BT or H12-BT isomers can be described by simple mixing rules with average absolute relative deviations of 0.022% and 0.38%. With increasing H2 pressure, the viscosity remains nearly constant, while the interfacial tension decreases by up to 5%. The thermal and mutual diffusivity of H12-ortho-BT containing dissolved H2 at 6 MPa decrease and increase with increasing temperature.
CRIS-Team Scopus Importer:2024-06-28
Keywords: Benzyltoluene; Hydrogen; Liquid organic hydrogen carrier; Mixture behavior; Regioisomers; Thermophysical properties